Evolving Knowledge: The Photography Practice of Contemporary Inuk Art Photographer Barry Pottle - Walsh, Andrea N. (KULA, 2021)
Interview with Inuk artist Barry Pottle from Nunatsiavut in Labrador (Rigolet). Photographs are selected from ten years of photography based on his experiences and observations as an urban Inuk. This conversation provides insight into Pottle’s photographic practice, particularly the artist’s process of learning the art and technical processes of photography and why his photographs matter in the process of Canadians facing their complicities in Canada’s ongoing colonialism. Pottle’s practice produces unique knowledge about Inuit culture and history through his eyes as an urban Inuk photographer.